Intelligent document capture with Ephesoft : learn to use open source software to automate the processing of scanned and digital documents to save time, save money, and improve accuracy /: learn to use open source software to automate the processing of scanned and digital documents to save time, save money, and improve accuracy. (2012) - Unknown
No abstract available